PENGEMBANGAN MODUL AJAR BIOLOGI BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - hayatun_nufus, rina (UNIVERSITAS HAMZANWADI, 2024)
This study aims to: (1) Develop a biology teaching module based on Problem Based Learning (PBL) to improve students' critical thinking. (2) To determine the feasibility and ideality of a biology teaching module based on Problem Based Learning (PBL) to improve students' critical thinking. (3) To determine the effectiveness of a teaching module based on Problem Based Learning (PBL) to improve students' critical thinking. This development research uses the Borg and Gall model which is carried out with 7 stages of development, namely: collecting initial information, planning, developing initial products, limited scale trials, product revisions, large scale trials, product revisions. The subjects of the trial in this study were material experts I and II, design material experts, 40 students of MA NW Sukamulia, and 28 SMAN 1 Lenek. Data collection techniques were carried out using questionnaires and data were analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the biology teaching module product Based on Problem Based Learning (PBL) to improve students' critical thinking skills is feasible, ideal and effective to be used during the learning process. This feasibility can be seen from the average percentage of feasibility from material expert I 93.06%, material expert II 96.99%, design expert 86.75%, and student response 79.67%. This has the criteria of very feasible and feasible. Furthermore, the ideality of the teaching module can be seen from the average score of ideality from material expert I 63, material expert II 66, design expert 68, and student response 54.05. This has the criteria of very ideal and ideal. Then the effectiveness of the teaching module can be seen from the average N-Gain obtained for the broad scale of the experimental class 0.62 and the limited scale of the control class 0.22. Based on the average N-Gain obtained, it has moderate criteria with a fairly effective level of effectiveness. Based on the results of the average percentage of the acquisition of Student Worksheets Based on Problem Based Learning (PBL) per group, it shows that Student Worksheets Based on Problem Based Learning (PBL) to improve students' critical thinking skills are in the very critical category. Keywords: Teaching Module, Student Worksheets, Borg and Gall, Problem Based Learning (PBL), Critical Thinking